A Multimodal Discourse Analysis of The English Textbooks’ Covers - Muhassin, Mohammad; Putri, Novi; Hidayati, Dewi Ayu; Pradana, Satria Adi (English Education: Jurnal Tadris Bahasa Inggris, 2022)
Multimodality has been studied in relation to a variety of text genres, but it has yet to be used to textbook covers. This paper is aimed at examining the representational meaning of visual resources in the covers of selected English textbooks and how the verbal and visual modes strengthen each other’s meaning. This is a qualitative research that uses a multimodal discourse analysis paradigm. Visual and verbal data were gained from two covers of selected English textbooks. The analysis includes representational meaning (Kress & van Leeuwen, 2006), text generic structure (Cheong, 2004),  and intersemiotic complementarity (Royce, 2007). The findings indicate that the representational meaning consists of  narrative and conceptual representations within the structures of   lead, display, announcement and emblem. Through the relationships of repetition, synonymy, and meronymy, verbal and visual modes help each other build cohesiveness. The cohesion signifies the relation between visual images and  verbal texts to convey meaningful messages of the covers. Certain implications were also elaborated in this study.